2017
DOI: 10.7773/cm.v43i2.2753
|View full text |Cite
|
Sign up to set email alerts
|

Microzooplankton grazing impact on the phytoplankton community at a coastal upwelling

Abstract: Microzooplankton grazing impact on the phytoplankton community at a coastal upwelling station off northern Baja California, MexicoImpacto del pastoreo del microzooplancton sobre la comunidad fitoplanctónica en una estación de surgencia costera localizada en la región norte de Baja California, México ABSTRACT. Experiments were carried out at a coastal upwelling site (ENSENADA station) off northern Baja California (México) during autumn 2015 (OCT-15) and spring 2016 (APR-16) to estimate phytoplankton daily growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Many of these investigations [14,25,26,28] reported the effect of these warm anomalies on sea surface temperature and phytoplankton biomass from the SCC southern region using information obtained from remote sensors. However, off the Baja California Peninsula, only the work of Linacre et al [30] and Jiménez-Quiróz et al [31] reported results regarding phytoplankton biomass and its taxonomic composition in consideration of field data from the entire water column; however, their work was based on a reduced number of cruises and a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these investigations [14,25,26,28] reported the effect of these warm anomalies on sea surface temperature and phytoplankton biomass from the SCC southern region using information obtained from remote sensors. However, off the Baja California Peninsula, only the work of Linacre et al [30] and Jiménez-Quiróz et al [31] reported results regarding phytoplankton biomass and its taxonomic composition in consideration of field data from the entire water column; however, their work was based on a reduced number of cruises and a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, was there a top‐down or bottom‐up control on the phytoplankton size‐structure in that period? Underlying factors invoked in modulating size‐structure in marine environments, include temperature (López‐Urrutia & Morán, 2015), sinking and grazing (Acevedo‐Trejos et al., 2015; Linacre et al., 2012, 2017) and changes in nutrient supply (Finkel et al., 2010; Marañon et al., 2012, 2014, and references therein). In the case of temperature, it is well known that this variable regulates the metabolic response of phytoplankton (e.g., Lewandowska et al., 2014; Sherman et al., 2016); however, phytoplankton metabolic rates increase with temperature only when nutrients are abundant (Marañon et al., 2012, 2014, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, zooplankton grazing "pushes" the phytoplankton community toward larger cell sizes (Acevedo-Trejos et al, 2013, and the apparent dominance of smaller size cells throughout the study (Figures 3c-3f) might suggest that zooplankton grazing was not a factor controlling size-structure of phytoplankton during the 2014-HW and El Niño events (Lavaniegos et al, 2019). However, in an experiment carried out in October 2015 (i.e., El Niño), Linacre et al (2017) reported that microzooplankton exerted an intense grazing pressure on phytoplankton biomass (>70% [Chl-a]) and daily primary production (>100% PP). Thus, their data suggest that the low Chl-a recorded during El Niño 2015 could also be explained by microzooplankton grazing, and thereby, this process cannot be completely ruled out.…”
Section: Shifts In Phytoplankton Community Structure Over the 2014-20mentioning
confidence: 93%
See 2 more Smart Citations